1.The given equation can be written as, "(D^{2}+6D+9)y = -xe^{4x}." The auxiliary equation is,
"m^2+6m+9=0." Solving we get, "m=-3(twice)". The complementary function is,
"y_{c} = (c_{1}+c_{2}x)e^{-3x}" . Let "y_{p} = (Ax+B)e^{4x}" be the trial particular solution.
Then, "y_{p}" satisfies the given differential equation. Therefore, "y''_{p}+6y'_{p}+9y_{p} = -xe^{4x}" .
Now,
"\\begin{aligned}\ny'_{p} &= e^{4x} \\cdot A+ (Ax+B)\\cdot e^{4x} \\cdot 4\\\\ &= e^{4x}(4Ax+A+4B)\\\\\ny''_{p}&= e^{4x} \\cdot 4A + (4Ax+A+4B)\\cdot e^{4x}\\cdot 4\\\\\n&= e^{4x}(16Ax+8A+16B)\n\\end{aligned}"
Hence,
"\\begin{aligned}\ne^{4x}\\bigg(16Ax+8A+16B+6\\cdot(4Ax+A+4B)+9 \\cdot (Ax+B)\\bigg) &= -xe^{4x}\\\\\n49Ax+14A+49B &= -x\\\\\n\\end{aligned}"
Comparing the coefficients and constant terms and solving we get,
"A = -\\dfrac{1}{49}, B = \\dfrac{2}{343}" . Therefore, "y_{p} = \\left(-\\dfrac{x}{49}+\\dfrac{2}{343}\\right)e^{4x} = -\\dfrac{e^{4x}}{49}\\left(x-\\dfrac{2}{7}\\right)" .
The general solution is,
"y = (c_{1}+c_{2}x)e^{-3x} - \\dfrac{e^{4x}}{49}\\left(x-\\dfrac{2}{7}\\right)"
2.The given equation can be written as, "(D^{3}-3D^{2}+3D-1)y=e^{x}-x+21". The auxiliary equation is "m^{3}-3m^{2}+3m-1=0." Solving we get, "m = 1 (thrice)." The complementary function is, "y_{c} = (c_{1}+c_{2}x+c_{3}x^{2})e^{x}." Since the complementary function is a linear combination of the term "e^{x}", we choose the trial solution as "y_{p} = Ax^{3}e^{x} + Bx + C."
Thus,
"\\begin{aligned}\ny'_{p} &= A(x^{3}e^{x}+3x^{2}e^{x})+B = Ae^{x}(x^{3}+3x^{2})+B\\\\\ny''_{p} &= A\\left(e^{x}(3x^{2}+6x)+e^{x}(x^{3}+3x^{2})\\right)\\\\\n&= Ae^{x}\\left(x^{3}+6x^{2}+6x\\right)\\\\\ny'''_{p} &= A\\left(e^{x}(3x^{2}+12x+6)+e^{x}(x^{3}+6x^{2}+6x)\\right)\\\\\n&=Ae^{x}(x^{3}+9x^{2}+18x+6)\n\\end{aligned}"
Using this in the given differential equation we get,
"\\begin{aligned}\ne^{x}\\bigg(Ax^{3}+9Ax^{2}+18Ax+6A\\\\ -3\\cdot(Ax^{3}+6Ax^{2}+6Ax) \\\\ +3\\cdot(Ax^{3}+3Ax^{2})-Ax^{3}\\bigg) \\\\ +3B - Bx - C &= e^{x}-x+21\\\\\n6Ae^{x}-Bx+(3B-C)&=e^{x}-x+21\n\\end{aligned}"
Comparing the coefficients, constant terms and solving we get,
"A=\\dfrac{1}{6}, B = 1, C = 18."
Hence, "y_{p}= \\dfrac{x^{3}e^{x}}{6}+x-18."
The general solution is,
"y=(c_{1}+c_{2}x+c_{3}x^{2})e^{x}+\\dfrac{x^{3}e^{x}}{6}+x-18."
Comments
Leave a comment